2005
DOI: 10.1111/j.1939-1676.2005.tb02654.x
|View full text |Cite
|
Sign up to set email alerts
|

Uses and Effectiveness of Pamidronate Disodium for Treatment of Dogs and Cats with Hypercalcemia

Abstract: Uncorrected hypercalcemia can cause clinical signs such as polyuria, polydipsia, vomiting, diarrhea, lethargy, and depression and contributes to the development of primary renal failure and soft tissue mineralization. Treatment of hypercalcemia includes diagnosis and treatment of the underlying disease process and some combination of excracellular fluid volume expansion by administration of fluids intravenously and administration of glococorticosteroids, salmon calcitonin, and furosemide. Bisphosphonates such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0
8

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 20 publications
0
35
0
8
Order By: Relevance
“…Pamidronate therapy has not previously been described in cancer-bearing cats; however, single dose intravenous pamidronate has been used to treat non-cancer-related hypercalcemia in three cats [18, 19]. One cat with idiopathic hypercalcemia developed moderate ionized hypocalcemia and worsening hypophosphatemia after pamidronate treatment [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pamidronate therapy has not previously been described in cancer-bearing cats; however, single dose intravenous pamidronate has been used to treat non-cancer-related hypercalcemia in three cats [18, 19]. One cat with idiopathic hypercalcemia developed moderate ionized hypocalcemia and worsening hypophosphatemia after pamidronate treatment [18].…”
Section: Discussionmentioning
confidence: 99%
“…One cat with idiopathic hypercalcemia developed moderate ionized hypocalcemia and worsening hypophosphatemia after pamidronate treatment [18]. One cat with nocardiosis developed mild reduction in total serum calcium but maintained normal ionized levels, and one cat with idiopathic hypercalcemia and chronic renal failure did not develop abnormal electrolyte changes [19]. Hypercalcemia was not a factor in our patient population, and no clinically significant reductions in calcium, phosphorus, or potassium were documented after pamidronate treatment in this population; however, feline hypercalcemia of malignancy related to malignant osteolysis may also represent a therapeutic target for pamidronate.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, research studies in animals and adults have demonstrated treatment with i.v. bisphosphonates to be effective and safe in hypercalcemic AKI as well as in those with underlying kidney disease [14,19,[24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…9 These drugs decrease osteoclastic activity, thus decreasing bone resorption. 9 These drugs decrease osteoclastic activity, thus decreasing bone resorption.…”
Section: Treatment Of Hypercalcemiamentioning
confidence: 99%